A COMPARISON OF COPING AND PERCEIVED STRESS AMONG STUDENTS BY FIRST GENERATION AND CONTINUING GENERATION STATUS, RACE/ETHNICITY, AND GENDER - Morgan, Annette L. (East Carolina University, 2014)
While the number of first generation and racial/ethnic minority students enrolled in higher education has increased over the past several decades, the level of stress students are reporting, compared to students in previous years has increased as well. Likewise, counseling center directors have seen an increase in the number of students with mental health issues, both as a percentage of the student population and in the severity of their illnesses. Therefore this study assessed how different student populations cope with stress. Also assessed was how diverse student populations perceive their general level of stress and if perception of stress influenced how they coped with stress. This quantitative study utilized the COPE to examine coping strategies, as well as the Perceived Stress Scale-10 to measure students' perception of stress. Research participants included 1,085 undergraduate psychology students from two southeastern universities. The sample was comprised of 38% (n=415) first generation students and 61% (n=665) continuing generation students. Participants were from six racial/ethnic groups; Black/African American, White, Hispanic of any race, American Indian/Native Alaskan, Asian, and students who self identified as being of two or more races. Statistical tests were conducted and results indicated there were more similarities between first generation and continuing generation students of different racial/ethnic groups, than there were differences in both coping and perceived stress. Results also indicated that both coping and perceived stress were not contingent on generation status and that few coping strategies were contingent on race/ethnicity and institution. However, the factor that was found to have the most significant relationship with both coping and perceived stress was gender. Possible explanations for differences as well as similarities in coping and perception of stress are discussed. This report concludes with recommendations for future research as well as implications for both college administrators and counseling center directors.
Keywords: Educational leadership; Coping; Gender differences; Perceived stress; Racial ethnic minorities; Stress (Psychology); Adjustment (Psychology); First-generation college students; Minority college students